2012
DOI: 10.1007/s00216-011-5686-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of beta endorphin metabolism in inflamed tissue, serum and trypsin solution by liquid chromatography–tandem mass spectrometric analysis

Abstract: Beta endorphin (β-END) is recognised as one of the most significant endogenous neuropeptides, responsible for a wide range of biological activities in the body. However, within the body β-END is exposed to hydrolysis by a variety of enzymes. In this study, we investigated the metabolism and fragmentation pattern of β-END in rat inflamed tissue, in rat serum and in trypsin solution. β-END (1-31)-rat was incubated at 37 °C in each matrix for different incubation times. The resultant fragments were separated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…A recent study in our laboratory has identified biotransformation fragments of BE 1–31 in rat inflamed tissue (Herath et al, 2012). This study demonstrated that the hydrolytic metabolism of BE 1–31 in homogenized inflamed tissue was faster than in serum and trypsin incubation; similar results have been noted for the processing of dynorphin (the endogenous ligand for KOR) within inflamed tissue homogenates (Morgan et al, 2012).…”
Section: Biotransformation Alteration In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in our laboratory has identified biotransformation fragments of BE 1–31 in rat inflamed tissue (Herath et al, 2012). This study demonstrated that the hydrolytic metabolism of BE 1–31 in homogenized inflamed tissue was faster than in serum and trypsin incubation; similar results have been noted for the processing of dynorphin (the endogenous ligand for KOR) within inflamed tissue homogenates (Morgan et al, 2012).…”
Section: Biotransformation Alteration In Diseasementioning
confidence: 99%
“…These acidic pH values have been shown to be concordant with those found within inflamed tissue (Dray, 1995). In addition, the nature of the biotransformation hydrolysis was altered, BE 1–31 was shown in inflamed tissue homogenates to be most susceptible for hydrolytic degradation at specific amino acid bonds: (Tyr1-Gly2), (Lys9-Ser10), (Leu17-Phe18-Lys19-Asn20), (Lys24-Asn25), (Lys28-Lys29-Gly30-Gln31) (Herath et al, 2012). This is likely to be a consequence of the inflammatory conditions that affect the enzymes independently and specifically (Lin et al, 2001).…”
Section: Biotransformation Alteration In Diseasementioning
confidence: 99%
“…A recent study in our laboratory has identified biotransformed fragments of BE 1–31 in rat serum, rat inflamed tissue, and following tyrosine hydrolysis in media [24]. This study demonstrated that the hydrolytic metabolism of BE 1–31 in homogenised inflamed tissue was faster than in serum and trypsin incubation.…”
Section: Introductionmentioning
confidence: 56%
“…It is well known that the pH at inflammation site is slightly lower59–61 than the normal physiological pH, which is around 7.4. In this study, we chose PBS whose pH was 6.4 as dissolution medium to investigate the release kinetic of both nanocarrier types simulated at comparable pH of the inflammatory tissues.…”
Section: Resultsmentioning
confidence: 99%